Implementation of Project-Based Learning in Vocational Education: Success Factors, Challenges, and Its Impact on Students' Competencies: A Systematic Literature Review - Wahyu Agil Masduki; Achmad Imam Agung; Yeni Anistyasari; Heru Arizal (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2026)
Vocational education has increasingly adopted Project-Based Learning (PjBL) as an instructional approach to strengthen students' technical capabilities while simultaneously fostering a wide range of professional competencies. Existing evidence, however, remains scattered across different vocational disciplines and educational contexts, limiting a comprehensive understanding of how PjBL has been implemented. This study presents a Systematic Literature Review (SLR) to examine the key success factors, implementation challenges, and educational impacts of Project-Based Learning within vocational education. The review was conducted in accordance with the PRISMA 2020 framework, with Scopus serving as the primary database for identifying relevant publications. Following the screening and eligibility process, 40 studies satisfied the inclusion criteria and were incorporated into the final qualitative synthesis. The synthesis identified project design, student collaboration, and technology integration as the principal factors associated with the successful implementation of PjBL. The most frequently reported challenges were student readiness, teacher readiness, and time constraints. In addition, the reviewed studies consistently demonstrated that PjBL enhances students' technical skills, soft skills, critical thinking, problem-solving abilities, and employability. Overall, the findings suggest that PjBL represents an effective pedagogical approach for advancing vocational education while equipping graduates to respond to evolving industrial requirements and technological change.